Potencial antileucêmico da lectina de Cratylia floribunda e sua conjugação com nanotubos de carbono - Lucena, Caio Cezar Oliveira de (2016)
Cancer is one of the biggest public health problems in the world, being the second cause of death worldwide. The search for new compounds that selectively promote cancer cells death is becoming a constant, as a strategy in the treatment of the disease. Lectins are a class of glycoproteins that recognize and bind specifically to carbohydrate clusters expressed on the plasma membrane. Carbon nanotubes have been gaining considerable attention because they are promising nanocarriers, enabling the conjugation of several molecules on their surface, improving drug delivery and specific cell recognition. In the present work, the cytotoxic activity of Concanavalin A and CFL lectins on chronic monocytic (K562) and acute monocytic (THP-1) promyelocytic leukemia cells was investigated. To evaluate cell viabillity, the MTT salt reduction was used, which show the metabolic ability of the cell to convert that salt to crystals. It was observed that lectins reduces the viability of the two tested cells lines. However, this cytotoxic effect was observed only after 72 hours of treatment. The lectins were also cytotoxic to non-cancerous HUVEC endothelial cells, but this response may have been due to the fact that these cells have several glycoconjugates expressed in their membrane. Using the trypam blue dye, which marks only cells with broken membranes, then unviable cells, it was also observed that the lectin-nanotube conjugate had no significant activity compare to that demonstrated by the lectin alone, suggesting that the nanotubes do not seem to improve the effect of the lectins. Investigating which way of death these lectins were activating by flow cytometer assays, it was observed that the cells demonstrate positive labeling for propidium iodide, indicating that the treatment of 72 hours caused damage to the cell membrane. However, using the tetramethylrhodamine methyl ester probe, it was seen that treatment with the lectins caused mitochondrial depolarization on K562 and THP-1 cells, a factor related to apoptosis. In addition, CFL lectin caused cell cycle arrest of THP-1 cells, promoting accumulation of cells in the G0/G1 phase. Thus, it was concluded that Concanavalin A and CFL lectins demonstrate a cytotoxic effect on leukemic cells, possibly through the induction of cell death by apoptosis in cells, due to the depolarization of the mitochondrial membrane, possibly blocking the expression of cyclins and CDKs, promoting cell cycle arrest in THP-1 cells. In K562, treatment with CFL for 72 hours may be activating some extrinsic pathway of apoptosis by membrane receptor, leading to depolarization of the mitochondria and consequently releasing apoptogenic factors, but without promoting cell cycle arrest. In this way, the lectins studied demonstrate an interesting antileukemic potential.